Powtoon-Based Animation Video to Improve Students' Learning Outcomes on Regional Artworks - Setiawan, Deni; Soniya, Erika (Journal of Education Technology, 2023)
IT-based learning media used by teachers are less varied and make students less enthusiastic about participating in learning so students do not understand the SBdP learning material. This study aims to develop Powtoon media for class V SBdP learning materials for regional artworks of class V. This research uses the Research and Development (R&D) development method. The subjects of this study were the fifth grade teachers and the fifth-grade students, totaling 43 students. Data collection carried out includes interviews, documentation, field observations or observations, and questionnaires on the needs of teachers and students. The data analysis technique was carried out with a feasibility test and media effectiveness test. The results of the feasibility test carried out by material experts and media experts got 85% and 91% results in the appropriate category. The results of the t-test obtained are 17.80774 and the n-gain test before and after learning is 0.68 with moderate criteria, so it is effectively used as a learning medium. The conclusion of this study is that the Powtoon animation video is declared feasible, and effectively used so that it can improve student learning outcomes for batik material as a work of regional art.